Persepsi Remaja Kota Purwokerto terhadap Konten Dark Joke pada Media Sosial Youtube - Agushar, Kent Benedict Zefanya; Sukendro, Gregorius Genep (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
With the development of the era, many new technologies have emerged in the field of information dissemination, one of which is social media. One of the social media that is currently being used by many people is Youtube. There are many kinds of content provided on Youtube social media, one of which is dark joke comedy content. Comedy dark jokes are humor or jokes based on eccentricities, mainly derived from negative things that happen in society with elements of irony, satire and satire. In this study, the researcher took one example from the content of Majelis Lucu entitled